2015
DOI: 10.15863/tas.2015.05.25.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Radiation on Some Hematological Parameters in Female Rats

Abstract: The effect of low exposure doses of gamma ray at doses of 0.055 Gy, 0.11 Gy and 0.165 Gy on the some hematological parameters of albino female rats were investigated. At the end of exposure periods and Blood samples were collected for analyses. The results obtained when increases of gamma ray doses of rats caused significant, p ≤ 0.05, decrease in the RBCs, Hb and Ht%. Also it was found elevation in MCV and MCH with increased exposure dose as well as significant decreases, p≤ 0.05, Platelets in decreasing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Previous studies have reported similar findings [6,17,30]. The observed decline in the white blood cell counts could be attributed to high radio-sensitivity of hematopoietic tissues [6,31]. The results are consistent with the previous findings that irradiation induces leucopenia and reduces lymphocytes, neutrophils and monocytes count [32,33].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Previous studies have reported similar findings [6,17,30]. The observed decline in the white blood cell counts could be attributed to high radio-sensitivity of hematopoietic tissues [6,31]. The results are consistent with the previous findings that irradiation induces leucopenia and reduces lymphocytes, neutrophils and monocytes count [32,33].…”
Section: Discussionsupporting
confidence: 89%
“…This probably could be because basophils naturally are rarely encountered granulocytes in the peripheral blood, therefore, it is not unusual for basophils to be absent [29]. Previous studies have reported similar findings [6,17,30]. The observed decline in the white blood cell counts could be attributed to high radio-sensitivity of hematopoietic tissues [6,31].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Ionizing radiation (IR) can cause changes in the chemical balance of cell and affects humans by depositing energy in body tissue [1]. Exposure to ionizing radiation increase the production of reactive oxygen species (ROS) such as superoxide (O 2-), hydroxyl radical (OH·) and hydrogen peroxide (H 2 O 2 ) and cause lipid peroxidation in cell membrane and damage to cellular activities leading to physiological disorders and dysfunction of cells and tissues [2].…”
Section: Introductionmentioning
confidence: 99%